Konseling Individual dengan Teknik Aversi untuk Menurunkan Perilaku Agresif pada Siswa Tunagrahita Ringan di SLB - Niswati, Hajra; Sinring, Abdullah; Latif, Suciani (Universitas Palangka Raya, 2025)
This study aims to evaluate the effectiveness of individual counseling with aversion techniques in reducing aggressive behavior in mildly disabled students. Aggressive behavior in mildly retarded students can hinder their emotional and social development, as well as negatively impact the surrounding environment. This study used a Single Subject Research (SSR) design with an A-B-A format consisting of three phases: initial baseline, intervention, and second baseline. The research subject was a seventh grade student at SLBN 1 Gowa who showed a high level of aggressiveness. Data were collected through direct observation and analyzed using visual analysis techniques and descriptive statistics to see patterns of behavior change. The results showed that aversion techniques were effective in reducing the intensity and frequency of aggressive behavior, with a significant decrease in the intervention phase. This decrease continued, albeit more slowly, after the intervention was stopped. In conclusion, aversion techniques proved to be effective in reducing aggressive behavior in mildly disabled students. For future research, it is recommended to use a larger sample and monitor behavioral changes in the long term to ensure the sustainability of the results achieved.